Sustainable agricultural production - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Will the present rate of expansion in global agricultural output be sufficient to satisfy the future demands of the world's burgeoning population and, more importantly, can improvements in productivity be sustained. Agriculturalists, ecologists and...